Fertilizers under pressure as U.S. tariffs reshape global input trade - Piñeiro, Valeria; Glauber, Joseph W.; Gianatiempo, Juan Pablo (Fertilizer Focus, 2025)
While food markets often dominate the headlines when trade tensions rise, the fertilizer market offers another way of looking at how agricultural systems absorb and respond to global policy shocks. Fertilizers are the backbone of modern food production, linking global energy markets, industrial supply chains, and agricultural productivity. When trade disruptions hit this sector, the consequences extend far beyond farm costs, influencing yields, price stability, and food security worldwide.